Pengembangan LKPD Berbasis Realistic Mathematics Education untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik - Sulistianti Siregar; Sapri Sapri (STKIP Andi Matappa Pangkep, 2021)
Development research aims to develop a valid, practical and effective Student Worksheet based on Realistic Mathematics Education to improve the mathematical problem solving ability of fourth grade students at the private elementary school of Muhammadiyah 1 Padang Sidempuan. The product developed is Worksheet teaching materials that contain fractional numbers and fractional forms. The development research model used is ADDIE which includes Analysis, Design, Development, Implementation and Evaluation. In this development, the researcher limits the development to the development stage. The instruments used consist of validity test sheets, practicality sheets and problem solving pretest and posttest questions. The data obtained from the validity, practicality and effectiveness were analyzed using descriptive statistical techniques. Based on the results of validity test, the RME-based Worksheet to improve problem-solving skills is in the very valid category with average score of 3.83 while the results practical test to improve problem-solving skills are in the very practical category with a score of 3.45 and The effectiveness of the Worksheet in terms of the pretest and posttest scores of students' learning outcomes obtained gain value of 0.65 in medium category with a percentage increase of 65% which means that it meets the effectiveness criteria.